THEORETICAL STUDY ON 15-CROWN-5 COMPLEX WITH SOME METAL CATIONS - Yahmin Yahmin; Harno Dwi Pranowo; Ria Armunanto (Indonesian Journal of Chemistry, 2012)
The capability of 15-crown-5 ethers to form complexes with some metal cations (Li+, Na+, K+, Zn2+, Cd2+ and Hg2+) was investigated by an ab initio quantum mechanical method. The calculations were performed at the RHF/lanl2mb level of theory. The interaction energies were used to evaluate the metal binding capability of the crown ether. The effect of nature of the metal on the binding properties was also studied. The results of the calculations showed that the interaction energy of the complexes increased in proportion with the ratio of ion charge, electronegativity and ionization potential to the cation diameter. In addition, based on the extraction distribution coefficient in the gas phase, it is found that the 15-crown-5 could not extract metal cations investigated.